PROBLEMS OF REVASCULARIZATION IN ACUTE MYOCARDIAL INFARCTION WITH ST SEGMENT ELEVATION - V. A. Ryabinin; P. Y. Lopotovsky; E. V. Migunova; A. P. Golikov; N. E. Kudryashova (Неотложная медицинская помощь, 2016)
SUMMARY. Based on the data of 370 patients with acute myocardial infarction with ST segment elevation, problems affecting the efficiency of revascularization treatment by PCI have been analyzed. It has been considered difficult to achieve further reduction in the timing of PCI compared to the available. The acceleration dynamics of ST segment on the electrocardiogram during PCI against thrombolysis and limitations of ECG monitoring during reperfusion in assessing myocardial perfusion have been specified. The necessity and appropriateness of PCI in different periods from the onset of MI have been reasoned. The prospects of using perfusion myocardial SPECT in assessing hypoperfusion and prognosis of restoration of myocardial function have been mentioned.